(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This research discovers the impact of Suggestopedia on vocabulary acquisition, listening comprehension and overall language engagement among intermediate and beginner and some advanced English level students from Uzbek nations utilizing a quantitative survey approach by Google Forms. Data was collected on students’ experiences with background music, guided images, and a distraction-free learning environment. The findings indicate that this method significantly supports to vocabulary retention, engagement, and motivation, particularly when authentic materials are carefully chosen to learners’ proficiency levels. By integrating organized original materials and multisensory techniques, Suggestopedia helps to be a bridge the gap between passive knowledge and active language use, eventually creating a more immersive and student-centered learning experience.